Peran Big Five Personality Traits terhadap Digital Stress pada Generasi Z - Kiranna Haddy; Roswiyani Roswiyani (Lembaga Yasin AlSys, 2026)
The increasingly intensive development of digital technology has heightened the risk of digital stress, particularly among Generation Z, who exhibit high levels of digital connectivity, while individual differences in responses to digital demands are presumed to be influenced by personality characteristics. This study aimed to analyze the role of the Big Five Personality Traits in digital stress among Generation Z in Indonesia. A quantitative approach with a correlational design was employed, involving 390 Generation Z individuals aged 18–28 years selected using non-probability sampling. Data were collected online using the Digital Stress Scale and The Revised NEO Personality Inventory (NEO-PI-R), then analyzed using linear regression to examine the contribution of personality traits to digital stress and differences in digital stress levels based on screen time duration. The results showed that the Big Five Personality Traits, taken together, played a significant role in digital stress with a contribution of 28.7%. Partially, neuroticism, extraversion, and conscientiousness had a significant positive effect on digital stress, whereas openness and agreeableness had a significant negative effect. In addition, differences in digital stress levels were found based on screen time duration, with individuals who spent more than six hours per day on screens tending to experience higher digital stress. The study concludes that personality is an important internal factor in explaining individual vulnerability to digital stress and highlights the importance of personality-based approaches in designing prevention strategies and intervention programs for managing digital stress, particularly among Generation Z.